Muon-spin relaxation study of the double perovskite insulators Sr2BOsO6 (B = Fe, Y, ln). (25th January 2016) - Williams, R C; Xiao, F; Thomas, I O; Clark, S J; Lancaster, T; Cornish, G A; Blundell, S J; Hayes, W; Paul, A K; Felser, C; Jansen, M
Abstract: We present the results of zero-field muon-spin relaxation measurements made on the double perovskite insulators Sr2 B OsO6 ( ). Spontaneous muon-spin precession indicative of quasistatic long range magnetic ordering is observed in Sr2 FeOsO6 within the AF1 antiferromagnetic phase for temperatures below K. Upon cooling below K the oscillations cease to be resolvable owing to the coexistence of the AF1 and AF2 phases, which leads to a broader range of internal magnetic fields. Using density functional calculations we identify a candidate muon stopping site within the unit cell, which dipole field simulations show to be consistent with the proposed magnetic structure. The possibility of incommensurate magnetic ordering is discussed for temperatures below K and 25 K for Sr2 YOsO6 and Sr2 InOsO6, respectively.